RELATED FACILITIES AND ACTIVITIES LANDING TO CATCH IN PORTOCEAN FISHING BELAWAN NORTH SUMATERA - Hariati Tanjung; Syaifuddin '; Bustari ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted on 17 - March 31, 2015. aims to determinethe type and capacity of facilities and relationships in existing fish landing sites inocean fishing port of Belawan, and beneficial for all parties, both readers,manager of the fishing port, fish landing sites and some information about thetype, capacity, condition and the level of utilization of the existing facilities in theport of Belawan Ocean Fisheries. Data obtained in the study of the 5 samplesTangkahan with the type of fishing gear used. The data obtained from therespondents are presented in tables and analyzed descriptively. Results of researchthat has been conducted addressing the relationship of facilities and activities atthe Port of landing catches of North Sumatra Belawan Ocean Fisheries that allfacilities used to help the process of landing. It's just that all the facilities areinadequate, pier length 154M all the activities carried out didermaga, not thedivision of each dock for various activities.Keyword : Facilities, landings